Psycho-Neuro-Autonomic Aspect of Burnout Syndrome: A Literature Review - Oliviera, Ivona; Ardani, Yanuar; Shatri, Hamzah (Stem Cell and Cancer Research (SCCR), 2023)
Background: Burnout syndrome are symptoms resulting from stress due to burden and stressors of high workload, as seen in health workers. Burnout syndrome can trigger psychological and physiological disorders, mainly related to the autonomic nervous system and the Hypothalamus-Hypophysis Axis pathway. Psychological disorders could be assessed using Maslach Burnout Inventory (MBI), while physiological disorders of the neuro-autonomic imbalance could be assessed using Heart Rate Variability (HRV). Aim: To study about the psycho-neurological aspect of burnout syndrome. Methods: A systematic literature review using the PRISMA method, through four stages, namely identification, screening, feasibility, and accepted results. Results: Literature search was performed using PubMed and Google Scholar databases. Seven articles fulfilled the inclusion criteria. Five out of seven articles showed association between HRV and burnout score, while two articles showed no association between HRV and burnout score. Discussion: In the presence of stress, the autonomic nervous system activates the amygdala and hypothalamus, which subsequently triggers response from the adrenal gland to produce noradrenaline, which in turn affects the autonomic nervous system. A low HRV signifies inflexibility of the sympathetic and parasympathetic nervous system. Contradicting results may be caused by difference in sample and HRV confounding factors such as difference of physical activity, exercise, underlying disease, medication. Conclusion: There is an association between burnout score and HRV, which implies the presence of neuro-autonomic dysfunction in burnout patients. Further research is needed to rule out confounding factors.